Linking auditor competence to audit quality: The moderating role of audit agility - Farida Hanum; Andri Zainal; Tapi Rumondang Sari Siregar; Muhammad Ridha Habibi; OK Sofyan Hidayat (Institute of Accounting Research and Novation (IARN), 2026)
The aims of this research to analyze the link of auditor competence and audit quality and to examine the role of audit agility as moderator in the link auditor competence and audit quality at KAP in Medan City. This study uses a questionnaire survey with purposive sampling of auditors who have used digital-based audit technology. Data analysis using SmartPLS 4.0 with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that auditor competence has a significant positive effect on audit quality. Audit agility is proven to strengthen the link of auditor competence on audit quality. More specifically, the findings suggest that the effect of auditor competence on audit quality becomes more optimal when supported by a high level of audit agility. Building on these findings, auditor competence significantly enhances audit quality, with audit agility further strengthening and optimizing this relationship, while control variables such as age, work experience, and professional certifications show no significant effect. These results imply that improving audit quality requires not only strengthening auditors’ competencies but also adaptive, responsive, and collaborative in audit practices.